2004
DOI: 10.1002/cne.20019
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the mRNA encoding prolyl endopeptidase in the rat brain and pituitary

Abstract: Prolyl endopeptidase (EC 3.4.21.26, PEP), a serine protease that hydrolyzes peptides at the carboxyl side of proline residues, is involved in the breakdown of several proline-containing neuropeptides and, thus, may contribute to the regulation of behavioral activities. In this study, the distribution of PEP mRNA was investigated in the central nervous system and pituitary of rat by means of quantitative reverse transcriptase-polymerase chain reaction analysis and in situ hybridization histochemistry. High dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 86 publications
4
38
1
Order By: Relevance
“…In the central nervous system, Prep mRNA was found in the hypothalamus (Fig. 1A), hippocampus, and cortex (5,6). Within the hypothalamus, higher expression of Prep mRNA was detected in the ventromedial nucleus (VMH) (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In the central nervous system, Prep mRNA was found in the hypothalamus (Fig. 1A), hippocampus, and cortex (5,6). Within the hypothalamus, higher expression of Prep mRNA was detected in the ventromedial nucleus (VMH) (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…In humans and rodents it is highly expressed in the brain (2), including the cortex, striatum, hypothalamus, hippocampus, and amygdala (3)(4)(5)(6). The physiological role of PREP remains elusive (7).…”
Section: Hypothalamic Prolyl Endopeptidase (Prep) Regulates Pancreatimentioning
confidence: 99%
“…However, the studies did not include the ovary and placenta for the assay and one report indicated that the ovary contained higher POP activity than the brain in the mouse (Ohta et al, 1992). In addition, many reports have suggested that POP enzymatic activity is not necessarily consistent with its mRNA level and protein amount (Bellemère et al, 2004;Garcia-Horsman et al, 2007;Irazusta et al, 2001;Myöhänen et al, 2007Myöhänen et al, , 2008a, possibly due to post-transcriptional or post-translational modifications or the existence of endogenous POP inhibitors (Salers, 1994;Soeda et al, 1985). Thus, what we can say from the current study is that at least in the mouse, POP mRNA is expressed at higher levels in the ovary and placenta than the brain.…”
Section: Discussionmentioning
confidence: 99%
“…In situ hybridization was performed as described previously (Bellemère et al, 2004). Briefly, sections were acetylated, treated with 0.2% Triton X-100 and covered with prehybridization buffer [50% formamide, 0.6 M NaCl, 10 mM Tris-HCl, pH 7.5, 0.02% Ficoll, 0.02% polyvinylpyrollidone, 0.02% bovine serum albumin (BSA), 1 mM EDTA, pH 8.0, 550 g/ml denatured salmon sperm DNA, and 50 g/ml yeast tRNA].…”
Section: Methodsmentioning
confidence: 99%